2019
DOI: 10.1016/j.celrep.2019.08.078
|View full text |Cite
|
Sign up to set email alerts
|

Etv1 Controls the Establishment of Non-overlapping Motor Innervation of Neighboring Facial Muscles during Development

Abstract: Highlights d Developing somatotopic facial motor neurons are transcriptionally diverse d Etv1 is required for dorsolateral facial-motor neuron migration and axon targeting d Axon mistargeting makes the eyelid muscle ''whisk'' in Etv1 mutants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
0
12
1
Order By: Relevance
“…LOCs and MOCs arise from a common progenitor pool with and develop alongside FMNs, raising the question of how OCNs deviate from a typical motor neuron fate to play such an unorthodox role in peripheral sensory modulation 9,10 . To learn more about the transcriptional origins of their unique developmental and mature properties, we compared all OCNs to a cluster of FMNs, which was identified based on co-expression of Etv1 and Epha7 ( Figure S2A, B ) 46 . Our analysis revealed substantial transcriptional differences between OCNs and FMNs that could contribute to their distinct functions and anatomy ( Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…LOCs and MOCs arise from a common progenitor pool with and develop alongside FMNs, raising the question of how OCNs deviate from a typical motor neuron fate to play such an unorthodox role in peripheral sensory modulation 9,10 . To learn more about the transcriptional origins of their unique developmental and mature properties, we compared all OCNs to a cluster of FMNs, which was identified based on co-expression of Etv1 and Epha7 ( Figure S2A, B ) 46 . Our analysis revealed substantial transcriptional differences between OCNs and FMNs that could contribute to their distinct functions and anatomy ( Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…This study identified a previously unknown role of Etv1 in SC differentiation and myelination. In contrast with other ETS domain TF superfamily members, Etv1 has been implicated in controlling the formation of functional connections between sensory afferents and motor neurons (17), the terminal maturation program of cerebellar granule cells (18), and the establishment of motor innervation of adjacent muscles (21). Based on the data analysis of gene expression profiles of myelinating SCs (Figure 1 and Table S1) and the in vitro and in vivo experiments, our study demonstrated that Etv1 depletion in SCs dramatically impairs SC proliferation, migration, and differentiation, and abrogates SC re-myelination in the regenerated sciatic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Etv1/Er81 as a member of the ETS family that is involved in the regulation of neuronal specialization, muscle spindle differentiation, and sensorimotor connectivity (17)(18)(19). The role of Etv1 has been studied primarily in a subpopulation of spinal motor neurons, and researchers have shown that the intrinsic expression pattern and cell body localization of Etv1 coordinates motor neuron process terminal arborization (20,21). Fleming and colleagues reported that Etv1 is required in a subset of the receptor tyrosine kinase positive (RET + ) mechanosensory neurons to form the functional pacinian corpuscles, which consists of a single myelinated axon and multiple layers of non-myelinating SCs (22).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, murine orthologue of up-regulated in kalirin–GEF1–inhibited cells ETV1 is expressed in the nuclei of mouse cranial nerves ( Zeisel et al, 2018 ). More precisely, Etv1 expression appears in facial motor neurons during the final post-tangential stage of their migration, the sub-nuclear segregation, and is indispensable for finalising neuronal differentiation ( Zhu & Guthrie, 2013 ; Tenney et al, 2019 ). Kalirin–GEF1 inhibition up-regulates low-risk specific transcriptomic traits in ADRN NB, which can be interpreted as a sign of a differentiation-like process.…”
Section: Discussionmentioning
confidence: 99%